Strong Convergence of Two-Dimensional Walsh–Fourier Series - Tephnadze, G. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We prove that certain means of quadratic partial sums of the two-dimensional Walsh–Fourier series are uniformly bounded operators acting from the Hardy space H p to the space L p for 0